2017
DOI: 10.1103/physrevapplied.8.034025
|View full text |Cite
|
Sign up to set email alerts
|

Improving Superconducting Resonators in Magnetic Fields by Reduced Field Focussing and Engineered Flux Screening

Abstract: We experimentally investigate superconducting coplanar waveguide resonators in external magnetic fields and present two strategies to reduce field-induced dissipation channels and resonance frequency shifts. One of our approaches is to significantly reduce the superconducting ground-plane areas, which leads to reduced magnetic field-focussing and thus to lower effective magnetic fields inside the waveguide cavity. By this measure, the field-induced losses can be reduced by more than one order of magnitude in m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Significant flux focusing from superconducting ground planes was recently investigated theoretically and experimentally in Ref. [35], where simulations gave F ≈ 27.5. The extent of flux focusing is specific to the device geometry; for example, features designed to trap flux can have large effects on F.…”
Section: B Hysteresis and Premature Switchingmentioning
confidence: 99%
“…Significant flux focusing from superconducting ground planes was recently investigated theoretically and experimentally in Ref. [35], where simulations gave F ≈ 27.5. The extent of flux focusing is specific to the device geometry; for example, features designed to trap flux can have large effects on F.…”
Section: B Hysteresis and Premature Switchingmentioning
confidence: 99%
“…Moreover, shielding may render devices useless in quantum sensing applications in which the purpose of the device is to sense the external environment. This has sparked research on further modifications to the device design and on understanding the effects of a magnetic field on different architectures of quantum circuits, including transmon qubits 156 and superconducting resonators 151,157 , which are integral components to readout.…”
Section: Vortices In Quantum Circuitsmentioning
confidence: 99%
“…However, Chiaro et al 160 showed that, without careful design, these features can increase the density of and subsequently losses from parasitic two-level fluctuators, thought to primarily form at surfaces and interfaces. Moreover, coplanar waveguide resonators were recently found to be more robust to external magnetic fields when the superconducting ground plane area is reduced, which lowers the effective magnetic field inside the cavity, and by coupling the resonator inductively instead of capacitively to the microwave feedline, shielding the feedline 157 .…”
Section: Vortices In Quantum Circuitsmentioning
confidence: 99%
“…This can lead to standing waves on the transmission line [31], and thereby can decrease the coupling between the resonator and the TL for the resonator being close to a magnetic field node of such a standing wave. One further issue, falsifying the extracted value of Q e , is the finite width of the ground planes of the TL, disabling proper grounding conditions, thereby supporting parasitic transmission through the sample holder [39,40], which in that case acts as a hol-low waveguide. Thus, some parasitic microwave power is transmitted from one port to the other, masking the ratio of off-resonance and on-resonance transmission, which, due to the fit with Eq.…”
Section: Simulation Vs Experimentsmentioning
confidence: 99%